Diagnosing and treating postpartum uterine artery pseudoaneurysm. Issue 1 (2nd January 2018) - Parr, Kathlyn; Hadimohd, Anisha; Browning, Adrianne; Moss, Jason
ABSTRACT: Uterine artery pseudoaneurysm (UAP) is an uncommon cause of postpartum hemorrhage. We present a case of a 19-year-old woman 6 weeks postpartum after low transverse cesarean delivery with recurrent heavy vaginal bleeding requiring a blood transfusion. Transvaginal sonogram revealed a UAP. Embolization of the uterine artery was performed, with resolution of her symptoms.